Mousie goes to Vigan - Barrera, Vicky Veloso; Fucio, Hubert B. (Quezon City LG & M, 2010)
In this charming story written by Vicky Veloso-Barrera and illustrated by Hubert B. Fucio, Mousie goes on a holiday in Vigan with Hannah and her family. Vigan is a beautiful place full of big old houses and museums. In Vigan, Mousie explores the town, eats delicious food like bagnet and ukoy, and rides a calesa with Hannah. Join Mousie on a Vigan adventure and have fun learning about this interesting place! (http://www.vibebookstore.com/mousie-goes-to-vigan.html)
Keywords: Children's stories, Philippine (English); Vigan (Ilocos Sur) -- Description and travel -- Juvenile literature